Complement system activation contributes to the ependymal damage induced by microbial neuraminidase. Issue 1 (December 2016) - Granados-Durán, Pablo; López-Ávalos, María; Hughes, Timothy; Johnson, Krista; Morgan, B.; Tamburini, Paul; Fernández-Llebrez, Pedro; Grondona, Jesús
Abstract Background In the rat brain, a single intracerebroventricular injection of neuraminidase fromClostridium perfringens induces ependymal detachment and death. This injury occurs before the infiltration of inflammatory blood cells; some reports implicate the complement system as a cause of these injuries. Here, we set out to test the role of complement. Methods The assembly of the complement membrane attack complex on the ependymal epithelium of rats injected with neuraminidase was analyzed by immunohistochemistry. Complement activation, triggered by neuraminidase, and the participation of different activation pathways were analyzed by Western blot. In vitro studies used primary cultures of ependymal cells and explants of the septal ventricular wall. In these models, ependymal cells were exposed to neuraminidase in the presence or absence of complement, and their viability was assessed by observing beating of cilia or by trypan blue staining. The role of complement in ependymal damage induced by neuraminidase was analyzed in vivo in two rat models of complement blockade: systemic inhibition of C5 by using a function blocking antibody and testing in C6-deficient rats. Results The complement membrane attack complex immunolocalized on the ependymal surface in rats injected intracerebroventricularly with neuraminidase. C3 activation fragments were found in serum and cerebrospinal fluid of rats treated with neuraminidase, suggesting that neuraminidase itself activates complement. In ventricular wall explants and isolated ependymal cells, treatment with neuraminidase alone induced ependymal cell death; however, the addition of complement caused increased cell death and disorganization of the ependymal epithelium. In rats treated with anti-C5 and in C6-deficient rats, intracerebroventricular injection of neuraminidase provoked reduced ependymal alterations compared to non-treated or control rats. Immunohistochemistry confirmed the absence of membrane attack complex on the ependymal surfaces of neuraminidase-exposed rats treated with anti-C5 or deficient in C6. Conclusions These results demonstrate that the complement system contributes to ependymal damage and death caused by neuraminidase. However, neuraminidase alone can induce moderate ependymal damage without the aid of complement.